Antimicrobial activity of edible coatings prepared from whey protein isolate and formulated with various antimicrobial agents - Ramos, Óscar L.; Santos, Arménia C.; Leão, Mariana V.; Pereira, Joana O.; Silva, Sara I.; Fernandes, João C.; Franco, M. Isabel; Pintado, Manuela E.; Malcata, F. Xavier (International dairy journal, 2012)
Using in vitro tests, the efficacy of edible coatings, made using whey protein isolates as a base material and glycerol as a plasticizer, and containing several antimicrobial compounds was assessed upon ubiquitous spoilage microflora in cheese. The formulation that showed the greatest activity was applied onto the surface of experimental cheeses, and their major microbiological and physicochemical features were compared with those of cheese added with commercial coatings. Chitooligosaccharide (COS) and lactic acid exhibited the highest (P<0.05) bacteriocidal effect against Gram-negative and Gram-positive bacteria, respectively, whereas sodium benzoate and COS exhibited the highest (P<0.05) inhibitory effect against the yeast. Combinations of lactic acid and COS yielded the highest (P<0.05) effect against all microorganisms tested; upon application on the cheese surface, they proved to be more active against bacteria, and less effective against yeasts and moulds (P<0.05) than their commercial coating counterparts.